A classification of bone tumors - Vyrva, Oleg; Golovina, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The main international classifications of tumours in the locomotor system were analysed. It was found out that the prognosis and course of tumours were most accurately and completely described by the WHO International Histological Classification of Tumours (2002), the TNM classification system (2002, 6th edition), the Enneking surgical staging system, the clinical-statistical classification, ICD-0 (1990, 2nd edition). The classifications play a key part in making diagnoses, helping oncologists to work following the same rules, improve old and introduce new methods of treatment.